Síntese de [1,2,3]triazoil[1,5-a]quinolinas promovida por base - Costa, Gabriel Pereira da (2021)
In the present work, we describe a method to obtain twenty-seven [1,2,3]triazoil[1,5-a]quinolines via organocatalysis through two successive cyclization reactions. The synthetic strategy primarily involves an intermolecular [3+2] cycloaddition between 1,3-dicarbonyl compounds (β-ketoesters and β- diketones) and o-carbonyl phenylazides, leading to the formation of triazole intermediates. A second sequential intramolecular cyclization reaction in the intermediate triazoles, in which the quinoline ring fused with the triazole nucleus, giving the products of interest. These reactions proceeded via formation of an enolate intermediate using 20 mol% of DBU as organocatalyst, in the presence of DMSO as solvent at 120 ºC for 24 h. This new metal-free method leads to the formation of products with yields ranging from low to excellent (~5-92%). The method can be used both for β-ketoesters alkyl-substituted, as for β-diketones alkyl/aryl-substituted. However the method was not efficient when β-ketoamides were used as substrates in this reaction. In a second moment, the extension of the previous method for the synthesis of [1,2,3]triazoil[1,5-a]quinoline 3-carboxamides was studied. In the new developed method the products of interest were efficiently obtained through a two-step synthetic strategy, in which the first step uses an organocatalyst, while the second one involves the use of an inorganic base. In this second report, thirteen examples of [1,2,3]triazoil[1,5-a]quinoline 3-carboxamides (secondary) were synthesized in yields ranging from good to excellent (63-96%) through the reaction between β-ketoamides (secondary) andix o-carbonyl phenylazides. These reactions were carried out in the presence of 10 mol% of diethylamine as an organocatalyst, DMSO as a solvent at 70 °C for 1 h (conditions for the formation of the triazole intermediate), followed by the addition of 1.2 equivalent of KOH in the reaction medium, leading to the formation of the products of interest after 1 h of reaction at 70 °C. The method was extended to tertiary β-ketoamides, in this case six examples of [1,2,3]triazoil[1,5-a]quinolines 3-carboxamides (tertiary) were obtained with yields ranging from moderate to good (48-76%). These compounds were synthesized through the reaction between tertiary β- ketoamides and 2-azidobenzaldehyde, under similar conditions to those used for secondary β-ketoamides. However, in these cases, DBU was used as organocatalyst instead of diethylamine. Similar results were obtained when 0.1 equivalent of KOH was used in the second reaction step, in which the products [1,2,3]triazolyl[1,5-a]quinolines 3-carboxamides (tertiary) were formed in yields of 40-70%